Is it good to be bad or bad to be good? Assessing the aggregate impact of abnormal weather on consumer spending - Anna Pauliina Sandqvist; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2018)
Although the influence of exceptional weather on individual behaviour has already been acknowledged in finance, psychology, and marketing, the literature examining weather effects at more aggregate level is still limited. Further, there is a lot of anecdotal evidence that weather anomalies affect consumer spending and retail business. The main aim of this analysis is to investigate and quantify the effects of unusual weather in consumer spending at macro-level. Using aggregate retail sales data for Switzerland, our findings reveal that weather deviations from seasonal norms, especially, unusually high or low temperatures in a given month, do cause sizeable intertemporal shifts in consumer spending at country level. Furthermore, the effects of abnormal weather are found to differ across seasons, both with respect to sign and magnitude. In particular, our findings indicate that weather effects manifest mainly through the seasons change channel: weather conditions in line with the coming season boost the purchases early in the season.
Keywords: E21; E32; D12; C22; 330; Consumer spending; intertemporal shifts; retail sales; unusual weather